Choices and personal maturity (Journal of Parents and Teachers, 2026)
Personal maturity develops through a balance—and sometimes a tension—between various alternatives. The author therefore proposes twelve pairs of alternatives that must be brought into harmony during the maturation process of every individual, and particularly that of children and adolescents, such as realism and idealism, creativity and discipline, and a positive self-image and an awareness of others.
Keywords: personal maturity; balance; personality